Inpatient cardiovascular medicine - Nallamothu, Brahmajee K.; Baman, Timir S. (Hoboken, New Jersey : Wiley Blackwell, 2014)
The first book developed specifically for hospitalists managing the growing number of patients with cardiovascular disorders Cardiovascular disease is a major cause of hospitalization and mortality worldwide, and will account for approximately twenty million deaths in 2015. Due to this growing problem, many patients are being managed by non-cardiovascular physicians in the inpatient setting. As a result, hospitalists and other inpatient physicians without specialized training in cardiology are faced with uncertainty when contemplating the proper management of these patients. This bo.
12.9 inpatient medical management -- floor status.
Online resource; title from PDF title page (Wiley, viewed on November 21, 2013).
Keywords: Cardiovascular system -- Diseases -- Treatment; Evidence-based medicine; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Cardiovascular system -- Diseases -- Treatment; Evidence-based medicine; Cardiovascular Diseases; Inpatients; Cardiovascular Diseases; Inpatients; Electronic books; Electronic books